Estudio comparativo del muro de hormigón armado y del muro reforzado con geosinteticos para la estabilidad del talud en el sitio crítico de la vía zhud – cochancay – el triunfo de la prov. cañar kilómetro 44 +680 - Falquez, Daniel (2011)
The following paper describes two soil containment systems for the critical site of the highway Zhud – Cochancay – El Triunfo. The first system consists in the slope’s stabilization by constructing a concrete wall, the second system includes stabilizing the slope through the formation of layers of compacted soil reinforced with geosynthetics. The design of both methods of soil containment and the comparison of the estimated costs are presented on this paper. With this preliminary analysis we will be able to recommend the best solution, both technically and economically.